Meat and fat productivity of pigs - Бірта, Г. О.; Бургу, Ю. Г. (Scientific Progress & Innovations, 2012)
Pigs of domestic and most foreign breeds, and also their crossbreeds are characterized by high precocity and suitability for all types of fattening. At the intensive fattening to 6–7 monthly age pigs have 100–120 kg of live weight, costs on 1 kg of liveweight gain are not more than 4,5 feed unit. Pigs which during the row of generations unsystematic bred in the conditions of bad feeding have such live weight only in age older than one year at an the expense of 1 kg of live weight gain 8–10 feed units and more. Meat of such pigs is rough, with the thick layer of hypodermic fat. With the improvement of feeding and terms of maintenance their precocity increases, but at the same time remains lower than animals’ which were systematically selected on higher precocity and high output of meat and which were bred in the conditions of the valuable feeding and proper maintenance.